ANALYSIS OF COAL MINING LAND USE CHANGES WITH THE DRIVING, PRESSURE, STATE, IMPACT, RESPONSE (DPSIR) APPROACH IN DAMAI DISTRICT, KUTAI BARAT REGENCY, INDONESIA - yunianto setiawan; Dwi Ermawati Rahayu; Edgar Rahman (Jurnal Infrastruktur, 2023)
West Kutai Regency, especially in Damai District, is one of the regions in Indonesia that has great potential for coal natural resources. Coal mining certainly requires sufficient space for its mining activities, therefore it is the regulation of space that will later regulate and limit the excessive use of land. This study uses the DPSIR method where the DPSIR component requires a response from the community. The criteria for resource persons are competent and have influence in making decisions regarding something related to environmental issues in Damai District. Furthermore, the selected resource persons must also be those who are willing to be interviewed. The driving of changes in the use of coal mining land in Damai District is due to demographic factors as well as economic growth. The pressure that occurs is in the form of land clearing and expansion of mining land, thereby reducing existing land resources and increasing mining activities, which in turn increases other environmental pressures. Other pressures, such as increasing waste disposal activities, increase the volume of waste due to the increase in the number of coal mining areas. The latest conditions, namely the results of monitoring the condition of the water and air are still quite good, it's just that in the waters of the Kedang Pahu River there are findings of iron content that still exceeds the threshold. The impact of the increase in mining land in the form of reduced land resources, increased potential for erosion that can cause flooding, reduced environmental quality and interfere